Effect of wollastonite microfibers as cement replacement on the properties of cementitious composites: A review. (20th November 2020) - He, Ziming; Shen, Aiqin; Lyu, Zhenghua; Li, Yue; Wu, Hansong; Wang, Wenzhen
Highlights: Wollastonite microfibers comprise a naturally occurring calcium metasilicate mineral. Wollastonite microfibers can be used as a partial substitute for Portland cement. The investigation recaps the fresh and hardened properties of cementitious composites. The opportunities and challenges for future developments are discussed. Abstract: The rapid development of the concrete industry consumes many natural resources and has many negative impacts on the environment. Large numbers of research attempts are focused on finding alternatives to cement and sand for use in concrete mixes to improve the sustainability of concrete. Wollastonite microfibers comprise a calcium metasilicate minerals with a wide range of sources and can be used as cement substitutes in cementitious composites, which has attracted worldwide attention in recent years. This paper presents the state-of-the-art research on the properties of cementitious composites containing wollastonite microfibers as partial cement replacement from the following aspects: setting time, workability, mechanical properties, shrinkage, durability, microstructural properties, environmental and economic analysis, and future prospects. The literature review confirms the feasibility of using wollastonite microfiber as a partial substitute for cement in cementitious composites, but this research still needs to be further studied and discussed.